The functionality of unit practice councils and its relationship with nurses' accountability: A cross‐sectional study - Mohammad Abu Dawass; Huthaifah Khrais; Ahmad Rayan; Mohammad Jaber (Nursing Open, 2023)
Abstract Aim This study aimed to examine the relationship between perceived unit practice councils' functionality and nurses' accountability in Saudi Arabia. Design A descriptive, correlational and cross‐sectional design was used. Methods Convenience sampling of 160 nurses working in multiple sites of a large, tertiary medical centre in Saudi Arabia was performed. Structured self‐administered questionnaires were used to measure perceived unit practice council functionality and levels of nurse accountability. Results Nurses perceived that unit practice councils had moderate levels of functionality; however, nurses had high levels of accountability. Also, perceived unit practice councils' functionality had a significant positive relationship with nurses' accountability (r = 0.49, p < 0.001). More studies are needed to investigate the impact of different shared governance models on nurses' work environments.